Effect of gypsum on soil potassium and magnesium status and growth of alfalfa - Syed‐Omar, S. R.; Sumner, M. E. (Taylor and Francis Group, 1991)
Though surface‐applied gypsum has been shown to be useful in reducing the subsoil acidity syndrome, excessive application could reduce the availability of other essential cations in soil. This study was conducted to determine the effects of surface‐applied gypsum on the availability of potassium (K) and magnesium (Mg) in field soils. Field experiments were conducted on Davidson and Tifton series soils in the southeastern United States with 6 main ameliorant treatments (0, 2, 5, and 10 t gypsum/ha, soil profile mixed to 1 m without lime incorporation and, mixed with lime to 1‐m depth), and 2 levels of Mg (0 and 100 kg Mg/ha) and 4 levels of K (0, 125, 250, and 375 kg K/ha) in a split‐split plot configuration. Alfalfa was grown on the Tifton soil and sorghum on the Davidson soil. Yields of alfalfa and sorghum increased with 2 t gypsum/ha but were adversely affected above 5 t gypsum/ha. Gypsum amendment at 2 t/ha reduced topsoil exchangeable Mg and K in both soils. In the soil profile study, exchangeable Mg was reduced throughout the upper 52.5‐cm depth, while no reduction of K was observed below the 22.5‐cm depth in either soil. The study indicates that Mg is more susceptible to leaching loss than K after surface application of gypsum. It is also suggested that surface‐applied gypsum be used as a soil ameliorant along with proper management of Mg and K fertilizers.